Multichannel radar receiver - Pravda, V.; Bychkov, V. (Видавництво Львівської політехніки, 2012)
Possible implementation of a numeral multichannel gauge of a radar signal arguments pointing on element baseline of chips FPGA is considered.
Keywords: multichannel radar receiver; radar; FPGA